PS-059 Conformity of the drug use process in patient care areas: a 5 year descriptive study. (25th February 2017) - Darbon, F; Jaatoul, M; Atkinson, S; Bussières, JF
Abstract : Background: Pharmacy practice is highly regulated and the drug use process is complex in patient care areas. Purpose: The objective of this study was to describe and compare conformity of the drug use process in patient care areas. Material and methods: This was a prospective, cross sectional, descriptive study conducted in inpatients care areas of a 500 bed teaching hospital. An audit was conducted annually. A paper checklist of 26–35 criteria grouped into 13 categories (eg, storage, waste, controlled substances, refrigerators, carts, automated dispensing cabinets, medication reconciliation, documentation, resuscitation carts, pharmacy intranet, abbreviations, antibiotics and high alert medications, hazardous drugs) was used. 2 research assistant evaluated conformity of each criteria per patient care areas (eg, compliant, partially compliant or not compliant). A conformity report was written, checked by decentralised clinical pharmacists and transmitted to patient care area managers with suggested corrective measures. Results: 27 patient care areas were audited each year from 2012 to 2016. Global conformity went, respectively, from 71%, to 65%, 78%, 64% and 62%. Between 2015 and 2016, a significant decrease in conformity was observed for the following 6 criteria: presence of a bin for pharmaceuticals wastes (89% in 2015 vs 62% in 2016, p<0.021), presence of a drug tray for resuscitation cart without expired drugs (100% vs 79%, p=0.016), nurses interviewed knew what to do in case of a technical problems with drug related technologies (19% vs 0%, p=0.017), or how to report an adverse drug reaction (19% vs 0%, p=0.017), where they can find antimicrobial drug use rules (63% vs 30%, p=0.024) and how to use personal protection equipment when administering hazardous drugs. A significant increase in conformity was observed for 2 criteria related to the medication reconciliation process. While this audit has been conducted for 5 years, we observed a decrease in global conformity that can be explained by the following: 9 criteria were added over time, conformity is difficult to reach for some criteria without technologies, a transfer to a new building is planned and staff can be less motivated to comply. Conclusion: Conformity of the drug use process in patient care areas did not improve over 5 years. No conflict of interest